Medan City Icon Image as Applied Art on Tourism T-Shirts - Diningrat, Raden Burhan Surya Nata; Priyatno, Agus; Muslim, Muslim (Gorga : Jurnal Seni Rupa, 2024)
The general aim of this research is to create a new design and apply it to typical Medan City souvenirs on T-shirts which are starting to be difficult to find. So that tourists who visit Medan can get a more interesting and varied variety of souvenirs, it will also support tourism in the city of Medan as well as become a reference for designers who want to develop a clothing business with characteristics typical of the city of Medan. The method used is a qualitative method, with a design thinking method approach consisting of the empathize, define, ideate, prototype and test stages. The results of the research are t-shirts as souvenirs, as a form of creativity that elevates the iconic shape of the city of Medan. Add value to souvenirs in the form of t-shirts that previously existed and add aesthetic value to t-shirt designs with Medan icons. Adding a variety of souvenir items to tourist destinations in the city of Medan.